VD_FINDINFO HC / 2010 / 165 vom 29. Januar 2010 - VD Tribunal cantonal (2010)
SURSIS À L'EXÉCUTION DE LA PEINE, PEINE PRIVATIVE DE LIBERTÉ, PEINE PÉCUNIAIRE | 41 ch. 1 CP, 41 ch. 2 CP, 411 let. h CPP, 411 let. i CPP, 415 CPP